Analisis Yuridis Undang-Undang No 8 Tahun 1999 Tentang Perlindungan Konsumen Terhadap Accountability Penjual Clouthing Line Terhadap Konsumen Akibat Barang Yang Cacat : (Studi Kasus SICKMYND) - Muhammad Sabrisa Khartanta Ginting Suka; Nirwan Junus; Dolot Alhasni Bakung (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This research aims to find out about the liability of clothing line sellers towards consumers due to defective goods in terms of Law No. 8 of 1999 on consumer protection, the Sickmynd case study. This research aims to determine the liability of clothing line sellers towards consumers who are harmed by defective goods as stipulated in Law Number 8 of 1999 concerning Consumer Protection. And to find out the factors that cause consumers to experience losses due to defective products when buying at SICKMYND Gorontalo. The method used in this research uses a normative type of researcher. Normative legal research is library legal research, namely research on primary data. What is studied are the rules written in laws, norms or other rules. Based on the results of research conducted, even though there are violations, this research highlights the responsibility of producers in overcoming consumer losses due to defective goods. Enforcement of the Consumer Protection Law is important to protect consumer rights and ensure balance in buying and selling relationships in the market. Violations of the Consumer Protection Law, especially Articles 8 to 17, were identified in the SICKMYND CLOTHING LINE business. The prohibition on producing and trading goods and services that do not comply with the standards, conditions and promises stated in labels or sales promotions is a violation that must be avoided by business actors.